ANALISIS KARAKTER DISIPLIN SISWA KELAS III PADA PEMBELAJARAN DI KELAS SD GMIT KALABALA - Magdalena Banakari; Yessy Mata; Nehemia Fanpada (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Classroom learning at SD GMIT Kalabala .The research employed a descriptive qualitive approach using observation,interviews ,and documentation techniques . The findings revealed that most students demonstrated positive disciplinary character though punctual attendance,compliance with school regualitions ,poper use of uniforms ,and responsibility in completing assingnments . However ,several students were still foud arriving late ,lacking concentration during lessons ,and submitting assignments beyond the required deadlines . Factors influencing disciplinary character included family environment ,teacher role modeling ,school culture ,and students learning motivation . Teachers played signitificant role through habituation , supervison ,and exemplary behavior . The study concludes that strengthening disciplinary character requires collaboration among scools , teachers ,and parents to create an ordely , comfortable ,and effective learning environment.